The role of Agr quorum sensing on sporulation and solvent formation in Clostridium beijerinckii - Boak, Lauren (2024)
In recent decades there has been a growing demand for the development of biofuels, in particular bioethanol and biobutanol. Such solvents can be produced via acetone-butanol-ethanol (ABE) fermentation in solventogenic Clostridium species. For solventogenic Clostridium, it has been shown that the switch from acidogenesis to solventogenesis and sporulation along with improved ABE productivity occurs at high cell density in batch culture, such as industrial fermentations, suggesting quorum sensing is involved. Whilst regulation of metabolism and sporulation via QS has been investigated in other clostridia, its role remains unclear in the industrially important species Clostridium beijerinckii.